Description of Intra-Annual Changes in Cambial Activity and Differentiation of Secondary Conductive Tissues of Aesculus hippocastanum Trees Affected by the Leaf Miner Cameraria ohridella - Elżbieta Myśkow (MDPI AG, 2021)
Aesculus hippocastanum trees are commonly infested by the leaf miner Cameraria ohridella, whose larval activity causes the destruction of the leaf parenchyma and induces defoliation. Pest attacks result in, e.g., production of smaller fruits and tree re-flowering in autumn. Concerning pest influence on stem structure only scarce information of narrower annual growth rings of wood has been published. Therefore, we determined the effect of the presence of the leaf miner infestation on intra-annual cambial activity and on differentiation of conductive tissues. These data were compared with phenological phases and pest activity. Pest feeding resulted in changes in onset, cessation and duration of cambial divisions, and differentiation of secondary xylem. The duration of cambial activity was about a month shorter in heavily infested trees and was connected with premature tree defoliation. Affected trees were characterised by a reduction in cambial divisions and earlier cessation of wood differentiation resulting in narrower wood rings. Furthermore, the infested trees exhibited altered wood structure, with more vessels of smaller diameters, however these changes did not affect its theoretical hydraulic conductivity. Interestingly, pest attack did not influence secondary phloem differentiation. The probable influence of long-term infestation on tree growth and condition was discussed.